MEASURING THE PROVINCIAL SHARIA HAPPINESS INDEX - Jebel Firdaus; Achmad Firdaus; Mahbubi Ali (Department Islamic Economics, 2022)
Purpose – This study aims to measure Sharia happiness index of 33 provinces in Indonesia from 2014 to 2017Design/methodology/approach – This research is descriptive with a quantitative approach, a modification of happiness index in 33 provinces in Indonesia conducted by BPS (Badan Pusat Statistik) published in 2014 and 2017 HLMS (Happiness Level Measurement Survey) by adding aspects that are in accordance with Sharia.Findings – Average happiness index for Indonesia based on BPS HLMS in 2014 was 68.79, increasing to 71.47 in 2017. The highest happiness index was province of North Maluku (73.12), and the lowest was province of Papua (64.25). Meanwhile, the average Sharia happiness index in Indonesia is 70.53. The highest average score was of Yogyakarta (74.11), and the lowest score was province of Papua (59.47).Research limitation/implication – The Government and Policy Stakeholders should pay attention and support to the factors that affect the level of religious satisfaction, which are proven to have a positive impact on the welfare and happiness of the community, where the majority of the Indonesian population is Muslim.Originality/value – Studies on sharia happiness at the provincial level are rare. Shariah happiness journals tend to discuss happiness at the conceptual level, very few describe Shariah happiness at the application level. This research enriches Islamic discourse in the context of macroeconomics which can be used as a reference for further research and studies.Keywords: Sharia, Happiness, Index, and quantitative